Aqueous fruit extract of Mimusops elengi causes reversible suppression of spermatogenesis and fertility in male mice. (14th January 2016) - Singh, N.; Singh, S. K.
Summary: Antifertility efficacy of oral administration of aqueous fruit extract of Mimusops elengi (200, 400 and 600 mg kg −1 body weight/day for 35 days) was evaluated in Parkes strain male mice. Various reproductive end points such as histopathology, sperm parameters, testosterone level, haematology, serum biochemistry and fertility indices were assessed; activities of 3β‐ and 17β‐hydroxysteroid dehydrogenases, and immunoblot expressions of StAR and P450scc in the testis were also assessed. Histologically, testes in Mimusops‐treated mice showed nonuniform and diverse degenerative changes in the seminiferous tubules; both affected and normal tubules were observed in the same sections of testis. The treatment had adverse effects on testicular hydroxysteroid dehydrogenases and StAR and P450scc, serum level of testosterone and on motility, viability and number of spermatozoa in cauda epididymis. However, serum levels of alanine aminotransferase, aspartate aminotransferase and creatinine, and haematological parameters were not affected by the treatment. Also, libido was not affected in treated males, but their fertility was markedly suppressed. By 56 days of treatment withdrawal, the alterations caused in the above parameters recovered to control levels, suggesting that Mimusops treatment causes reversible suppression of spermatogenesis and fertility in Parkes mice. Further, there were no detectable signs of toxicity in treated males.